Determinant Factors Of Profitability Of Islamic Banks In 2017-2021 With Capital Adequacy Ratio As a Variable Intervening - Eka Wita Sari; Ahmad Irvani; Reka Meilani; Hendra Cipta (Al-bank: Journal of Islamic Banking and Finance, 2023)
This study aims to analyze the effect of Non Performing Financing (NPF) and Finance to Deposit Ratio (FDR) on Islamic bank profitability mediated by Capital Adequacy Ratio (CAR). This study uses secondary data in the form of panel data (pooled data), which is a combination of cross section data and time series data. The analysis technique uses path analysis. The results showed that FDR has no influence on CAR while NPF affects the CAR of Islamic banks. FDR and NPF directly have no influence on the ROA of Islamic banks. CAR variable is only able to be intervening between NPF and ROA while FDR variable indirectly through CAR variable has no significant effect on ROA of Islamic banks.